2011
DOI: 10.1128/aac.01119-09
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Mutation Rate Depends on agr Locus Expression during Oxacillin-Mediated Heterogeneous-Homogeneous Selection in Methicillin-Resistant Staphylococcus aureus Clinical Strains

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) strains are characterized by a heterogeneous expression of resistance. We have previously shown in clinical oxacillin-susceptible, mecA-positive MRSA strains that selection from a very heterogeneous (HeR) to highly homogeneous (HoR) resistant phenotype was mediated by acquisition of mutations through an oxacillin-induced SOS response. In the present study, we used a spotted DNA microarray to evaluate differential gene expression during HeR-HoR selection and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Second, in studies published by our group, we showed that ␤-lactam-mediated HeR/HoR selection required increases in both expression of mecA and mutagenesis in order to achieve the selection of the highly resistant HoR phenotype (13,14). In the current study, and based on the mechanism of action of CPT, we determined that mecA plays a pivotal role during the selection process.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Second, in studies published by our group, we showed that ␤-lactam-mediated HeR/HoR selection required increases in both expression of mecA and mutagenesis in order to achieve the selection of the highly resistant HoR phenotype (13,14). In the current study, and based on the mechanism of action of CPT, we determined that mecA plays a pivotal role during the selection process.…”
Section: Discussionmentioning
confidence: 83%
“…Three independent cultures were sampled in triplicate to minimize error caused by inter-and intrasample variation during the HeR/HoR selection process. Inoculated flasks were incubated at 37°C with shaking at 145 rpm; aliquots of 100 l were taken at different time intervals, including 6, 27, and 33 h, as we previously described (13,14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heteroresistance to homogeneous high-resistance selection (HeR-HoR selection) by oxacillin was associated with an increased mutation rate and expression of mecA and the SOS response lexA/recA gene regulators (129). Increased expression of the agr (accessory gene regulator) system during HeR-HoR selection was required to tightly modulate SOS-mediated mutation rates, which then led to full expression of homogeneous oxacillin resistance in very heterogeneous clinical MRSA strains (130). The PBP1 protein played a role in SOS-mediated RecA activation and HeR-HoR selection (131).…”
Section: Heteroresistance To ␤-Lactamsmentioning
confidence: 99%